Building Resilience in Large High-Technology Projects: Front End - Crosby, Phil (IGI Global, 2012)
Success in mega-projects is frequently discussed among project theoreticians and practitioners. This research focuses on high-technology projects and draws on recent literature and fieldwork at ten contemporary mega-science projects in Chile, Australia, and Europe. This study concludes that project success is not random and early adoption of certain approaches, activities, and launch conditions will position a project for success and resilience. Nine resilience factors (beyond a priori programmatical artefacts) are grouped into three ‘attitudinal’ factors, and six ‘conditioning’ factors and then examined in detail against three case study projects. The study’s conclusion show that attitudinal factors remain a challenge, especially within institutional type high-tech projects, and launch conditioning shows mixed levels of application. Through the nine factors, this paper offers newly consolidated insights for high-tech project start-ups and presents the case for co-application of contingency funding and ‘proto’ task forces in response to unknown risks, and advocates the establishment of more formal information ‘traffic’ management through an empowered centralised project information office.